2003
DOI: 10.1097/01.ede.0000041256.12192.23
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Food Frequency Questionnaire in Preschool Children

Abstract: The FFQ shows mostly good agreements with multiple 24-hour recalls and biomarkers in preschool children. In addition, the validity of the FFQ using parental report does not appear to be compromised when there are meal providers in addition to the parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
109
3
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 17 publications
15
109
3
3
Order By: Relevance
“…The correlation between energyadjusted intake of fat measured by 24 h recalls and by FFQ was 0.39 (Po0.05) (Parrish et al, 2003). Comparisons of PUFA intake were not performed in this study.…”
Section: Food Frequency Questionnairementioning
confidence: 74%
See 1 more Smart Citation
“…The correlation between energyadjusted intake of fat measured by 24 h recalls and by FFQ was 0.39 (Po0.05) (Parrish et al, 2003). Comparisons of PUFA intake were not performed in this study.…”
Section: Food Frequency Questionnairementioning
confidence: 74%
“…This FFQ was designed based on American diets and may not be valid in other countries. Although developed for use with adults, it has been minimally altered and validated in samples of children (Stein et al, 1992;Parrish et al, 2003). The caregivers of all participants were sent the 111-item FFQ asking them to record their child's diet in the previous year.…”
Section: Food Frequency Questionnairementioning
confidence: 99%
“…§'De-attenuated FV-adjusted' is the FV-adjusted correlations adjusted for the within-person variation occurring between the five days of diet record and two administrations of the FFQ for each participant. ||The range of correlations from six multi-nutrient FFQ validation studies in toddlers 12-24 months old (6)(7)(8)(9)(10)(11) . Three studies reported Spearman's correlations (7,9,10) , two studies reported Pearson correlations (6,11) and one study reported energy-adjusted Pearson correlations (8) .…”
Section: Relative Validitymentioning
confidence: 99%
“…multivitamins). We conducted a validation study in 68 DAISY children, in which the nutrients obtained from the FFQ were compared with those obtained from four 24-hour recalls throughout the corresponding year, and were found to be significantly correlated 11 . Data were collected to evaluate the subject's exposure to environmental tobacco smoke (ETS) via a questionnaire that inquired about whether either the child's parents smoked inside or outside the home.…”
Section: Questionnaire Datamentioning
confidence: 99%